ANALISIS HUKUM PENGADOPSIAN ANAK DARI KORBAN TSUNAMI PALU DITINJAU DARI PP NO. 54 TAHUN 2004 TENTANG PELAKSANAAN PENGANGKATAN ANAK - Surya Insani Kamil; Kaleb Othniel Aritonang (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The adoption of children who are victims of the Palu tsunami presents a complex issue within the legal framework of adoption in Indonesia. Government Regulation No. 54 of 2004 serves as a crucial legal foundation; however, the prohibition of adopting tsunami victim children by the Minister of Women's Empowerment and Child Protection has sparked controversy. This study aims to analyze the legal aspects concerning the adoption of children from the Palu tsunami victims within the context of Government Regulation No. 54 of 2004. The research employs a normative juridical approach, focusing on the analysis of legislation related to child adoption. The findings indicate the necessity for effective coordination between government agencies and the community in handling cases of child adoption from natural disaster victims. The implementation of Government Regulation No. 54 of 2004 needs to be strengthened through a thorough understanding of the principles of adoption law and child protection. Joint efforts are required to ensure that the adoption process is conducted effectively and in accordance with applicable legal provisions, with attention to the best interests of the child in line with the principles of the Convention on the Rights of the Child.